THE MMR VACCINE AND AUTISM: SCIENTIFIC ILLITERACY AND IRRESPONSIBILITY OF MASS MEDIA THREATENS PUBLIC HEALTH - V.К. Tatochenko; A.V. Goldstein (Union of pediatricians of Russia, 2010)
In this article, leading Russian scientists call on the medical community to critically treat the information circulated by mass media regarding vaccinal prevention in particular, and any other information in general. There are multiple examples of adverse influence of misleading information on the fates of many hundreds of people. At the same time the authors demonstrate that so-called scientists, professionals, whose opinion are trusted not only by regular people, but also by physicians who become their followers spreading misconceptions, may very well be dishonest to their nation. Key words: vaccinоprophylaxis, misconceptions, complications, children. (Pediatric Pharmacology. - 2010; 7(2):33-35)